Proceedings of the 21st Conference on Computational Natural Language Learning (CoNLL 2017) 2017
DOI: 10.18653/v1/k17-1007
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Partitioning for Coreference Resolution

Abstract: This paper presents a collaborative partitioning algorithm-a novel ensemblebased approach to coreference resolution. Starting from the all-singleton partition, we search for a solution close to the ensemble's outputs in terms of a task-specific similarity measure. Our approach assumes a loose integration of individual components of the ensemble and can therefore combine arbitrary coreference resolvers, regardless of their models. Our experiments on the CoNLL dataset show that collaborative partitioning yields … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Given the above, we can conclude that the input that our mention detector receives has a substantial impact on mention detection errors. This is also pointed out by Uryupina and Moschitti (2013), who suggest that better performance can be obtained if a robust preprocessing is achieved. The performance of the mention detector is highly dependent on the preprocessing tools, and errors caused by these tools are difficult to tackle.…”
Section: Error Analysismentioning
confidence: 62%
See 1 more Smart Citation
“…Given the above, we can conclude that the input that our mention detector receives has a substantial impact on mention detection errors. This is also pointed out by Uryupina and Moschitti (2013), who suggest that better performance can be obtained if a robust preprocessing is achieved. The performance of the mention detector is highly dependent on the preprocessing tools, and errors caused by these tools are difficult to tackle.…”
Section: Error Analysismentioning
confidence: 62%
“…In end-to-end coreference resolution systems, low recall in the mention detection step has negative effects on the whole process, since missed mentions are not available for coreference resolution in the later stages. As is pointed out in Uryupina and Moschitti (2013), in the CoNLL 2011 shared task the majority of the participants relied on rule-based modules to obtain mention boundaries for English. However, in the CoNLL 2012 shared task, participants with rule-based systems fell back to very simple baselines in mention detection, which demonstrated that rule-based systems are not easily adaptable to languages other than the one for which they were created.…”
Section: Related Workmentioning
confidence: 92%